a) - (5x +2 ) = 2x - 2 b) x + 12 = + 8 c) - 2x + 5 = -3 d) 3x - 4 = x - 15 e) - 2 ( + 3x - 4 ) = 3x - 1 f) - x + 3 = - 13
São equações de 1° Grau
Arnaldo62:
Equações de 1º Grau
Respostas
respondido por:
0
Explicação passo-a-passo:
-(5x+2)=2×-2
-5x-2=2x-2
-5x=2x
-5x-2x=0
-7x=0
x+12=+8
x=12-8
x=4
-2x+5=-3
-2x=-3-5
-2x=-8
x=-4
3x-4=x-15
3x-x=15+4
2x-11
11/2 ou 5,5
-2(+3x-4)=3x-1
-6x+8=3x-1
-6x-3x=-1-8
-9x=-9
x=1
x+3=-13
x=-13-3
x=16
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás